Spatial distribution and reduction of PCDD/PCDF Toxic Equivalents along three shallow lowland reservoirs - Urbaniak, M. (Springer Berlin Heidelberg, 2013)
Reservoirs situated along a river continuum are ecosystems where rates of transfer of suspended matter and associated micropollutants are reduced due to sedimentation, accumulation, and biological and physical transformation processes. Among the micropollutants, PCDDs and PCDFs are substances that are highly toxic and carcinogenic for humans and animals. They are emitted and dispersed in the environment throughout the whole catchment area and may accumulate in aquatic and terrestrial food chains, creating a risk for human health. A wealth of data exists indicating the increase in the concentrations of pollutants along a river continuum. A comparative analysis of total, individual, and TEQ PCDD/PCDF concentrations in large lowland, shallow reservoirs located in different catchments (“I”—industrial/urban/agricultural, “U”—urban/agricultural, and “A”—agricultural/rural) showed decreases of the TEQ concentrations in bottom sediments along a gradient from the middle sections to the dam walls. Moreover, penta-, hexa-, and heptachlorinated CDD/CDF congeners were reduced from 28.8 up to 93.6 % in all three types of reservoirs. A further analysis of water samples from the inlets and outlets of the “A” reservoir confirmed this tendency.